Peran Dimensi Komitmen sebagai Faktor Pengaruh dalam Membangun Loyalitas - albari, Albari (Jurnal Aplikasi Manajemen, 2012)
The importance of the organization to build commitment all target markets increasinglynecessary as part of a marketing strategy to maintain effective long-term relationship, asreflected by the loyalty market. To measure the magnitude of the role that market commitment is necessaryto identify through research the dimensions of affective commitment, calculative and goal commitment onloyalty, in addition to the antecedent factors of service quality and reliability. The research was carriedout by involving students at a private college (PTS) of the Yogyakarta. The results show the importanceof the role of affective commitment dimension and level of trust as a mediator variable to the buildstudent loyalty. Predicted size of student loyalty is also directly contributed by the quality of service hasbeen provided by management and the level of student goal commitment.